A Review of Communication, Body Language and Communication Conflict - Uzun, Gizem Öneri (International Journal of Psychosocial Rehabilitation, 2020)
The term "communication" has been derived from the Latin "communis," that means "common". Thus "to communicate" means "to make common" or "to make known", "to share" and includes verbal, non-verbal and electronic means of human interaction. Every communication involves one sender, a message and a recipient, through verbal or nonverbal means, including speech, or oral communication; writing and graphical representations, signs and signals and specially the behaviors. This may sound simple, but communication is actually a very complex subject, and more simply, communication is said to be the creation and exchange of meaning. There are four types of communication in which they are intrapersonal communication, interpersonal communication, group communication and mass communication. Information can be shared several different ways with one another. For example, using verbal communication when sharing a presentation with a group; you might use written communication when applying for a job or sending an email to a lecturer. So, there are verbal, non verbal, visual and written skills in communication. Communication is carried out in two ways: verbal and non-verbal. The means of expression of non-verbal communication are the head, face, various parts of the body or the body itself as a whole. Body language, which is the most basic element of nonverbal communication, is a form of communication with gestures, mimics and body movements. Communication is also a term that has various definitions reflecting different perspectives. "Communication is a transactional process in which individuals create, share and regulate meaning," as defined in Family Communication. Family is a basic social unit that involves people at multiple levels. After leaving their family of origin most people start a new family of orientation.